Management and use of organic solid waste during the period 2013-2016 at Universidad Nacional - Rojas-Vargas, Julián (2020)
The objective of this study was to analyze the management and use of organic solid waste through generation rates by type of waste in the sodas of the Campus Omar Dengo of the National University of Costa Rica. The raw and cooked residues were collected in five sodas, weighed and based on this data, daily waste generation rates were calculated. In addition, a survey was conducted in order to determine the perception of users about this problem. It was evidenced that the amount of waste varied significantly during the sampling period and it varies in each soda. Social aspects, as well as quality and proximity, induce greater user assistance; therefore, the generation of waste is increased. It is concluded that it is necessary deeper studies that allow the reduction of waste, as well as the awareness of the users of the sodas